2013
DOI: 10.4103/1119-3077.110142
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of undernutrition among primary school children residing in slum areas of a Nigerian city

Abstract: This study highlights the need for an effective nutrition program targeted at school children in urban slums surrounded by factors predisposing them to undernutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 10 publications
7
28
0
Order By: Relevance
“…It is because health friendly measurement is more likely to be adopted by educated mothers and so better nourished children's mothers had better health friendly attitude. Moreover, literate mothers are also better able to manage meager resources to provide essentials and thus having healthier child [27]. This finding is similar to other studies on childhood malnutrition, which showed prevalence of malnutrition was influenced by maternal formal education.…”
Section: Significance Levelsupporting
confidence: 82%
“…It is because health friendly measurement is more likely to be adopted by educated mothers and so better nourished children's mothers had better health friendly attitude. Moreover, literate mothers are also better able to manage meager resources to provide essentials and thus having healthier child [27]. This finding is similar to other studies on childhood malnutrition, which showed prevalence of malnutrition was influenced by maternal formal education.…”
Section: Significance Levelsupporting
confidence: 82%
“…On the contrary, several studies have reported that socioeconomic status is a strong predictor of both nutritional status (Brooks-Gunn and Duncan, 1997;Ndukwu et al, 2013) and outcomes in children (Bradley and Corwyn, 2002;Santos et al, 2008). The lack of an association between household wealth and child outcomes is not without precedence; an earlier study among infants living within the same context (Abubakar et al, 2008) has reported similar findings.…”
Section: Discussionmentioning
confidence: 45%
“…Mendez and Adair (1999) found that children who started school at earlier ages (5 or 6 years) were substantially taller than children who started school later (7 or 8 years) so it may be that better-off children enrol in school at earlier ages. And although children in low income settings may all suffer the effects of deprivation, those from the least wealthy households in low income settings are more likely to be malnourished (Sigman et al, 1989;Brooks-Gunn and Duncan, 1997;Bradley and Corwyn, 2002;Abubakar et al, 2008;Ndukwu et al, 2013). Rural residence (Hautvast et al, 2000;Nabag, 2011) and a reduced likelihood of attending school (Ivanovic et al, 2012) have also been related to poor nutritional status.…”
Section: Human Neurosciencementioning
confidence: 99%
“…Previous study by authors among primary school children in Nigerian city projected a highly significant association between slum children and malnutrition [26]. Another previous study by authors predicted a significant correlation between area of inhabitation of children (ruralurban) and undernourishment of children [27].…”
Section: Discussionmentioning
confidence: 94%